Effects of a phosphocitrate analogue on osteophyte, subchondral bone advance, and bone marrow lesions in Hartley guinea pigs. Issue 2 (February 2018) - Sun, Y.; Kiraly, A. J.; Sun, A. R.; Cox, M.; Mauerhan, D. R.; Hanley, E. N.
Abstract : Objectives: The objectives of this study were: 1) to examine osteophyte formation, subchondral bone advance, and bone marrow lesions (BMLs) in osteoarthritis (OA)-prone Hartley guinea pigs; and 2) to assess the disease-modifying activity of an orally administered phosphocitrate 'analogue', Carolinas Molecule-01 (CM-01). Methods: Young Hartley guinea pigs were divided into two groups. The first group (n = 12) had drinking water and the second group (n = 9) had drinking water containing CM-01. Three guinea pigs in each group were euthanized at age six, 12, and 18 months, respectively. Three guinea pigs in the first group were euthanized aged three months as baseline control. Radiological, histological, and immunochemical examinations were performed to assess cartilage degeneration, osteophyte formation, subchondral bone advance, BMLs, and the levels of matrix metalloproteinse-13 (MMP13) protein expression in the knee joints of hind limbs. Results: In addition to cartilage degeneration, osteophytes, subchondral bone advance, and BMLs increased with age. Subchondral bone advance was observed as early as six months, whereas BMLs and osteophytes were both observed mainly at 12 and 18 months. Fibrotic BMLs were found mostly underneath the degenerated cartilage on the medial side. In contrast, necrotic BMLs were found almost exclusively in the interspinous region. Orally administered CM-01 decreased all of these pathological changes and reduced the levels of MMP13 expression. Conclusion: Subchondral bone may play a role in cartilage degeneration. Subchondral bone changes are early events; formation of osteophytes and BMLs are later events in the OA disease process. Carolinas Molecule-01 is a promising small molecule candidate to be tested as an oral disease-modifying drug for human OA therapy. Cite this article : Y. Sun, A. J. Kiraly, A. R. Sun, M. Cox, D. R. Mauerhan, E. N. Hanley Jr. Effects of a phosphocitrate analogue on osteophyte, subchondral bone advance, and bone marrow lesions in Hartley guinea pigs. Bone Joint Res 2018;7:157–165. DOI:10.1302/2046-3758.72.BJR-2017-0253.